Румънската и съветската политика за българите в Бесарабия в периода 1918-1944 г - Hatłas, Jerzy (My University, 2013)
The article covers the subject of the Romanian and Soviet authorities policy towards Bulgarians living in Bessarabia between 1918 and 1944. This period was not easy for Bulgarian diaspora. The Soviet period (1940-1941), was a time of victimization and human rights violation, whereas Romanian authorities’ policy (1918-1940) evolved from liberal to repressive. Only the period between 1941 and 1944 can be assessed as an unequivocally bad, when Bessarabia was included within the borders of Romania again.